2.13. Rozwiąż równania: a) 2 ^ 17 * x – 16 ^ 4 * 3 = 5(4 ^ 8 * x – 3 * 2 ^ 17) ) c) 3 ^ 13 * x – 4 * 9 ^ 6 = 27 ^ 4 * (2x – 5) e) x/(2 ^ 5) + (1/4) ^ 2 = (- 1/8) ^ 2 * x + 1/(2 ^ 3) b) 27 ^ 3 * 2 * x – 3 ^ 1 = 3 ^ 10 * x + 2 * 3 d) (4 ^ 5 * x + 32 ^ 2) * 2 ^ 5 = 2 ^ 16 . f) x/(4 ^ 4) – 1/((- 2) ^ 6) = – (- 1/16) ^ 2

2.13. Rozwiąż równania: a) 2 ^ 17 * x – 16 ^ 4 * 3 = 5(4 ^ 8 * x – 3 * 2 ^ 17) ) c) 3 ^ 13 * x – 4 * 9 ^ 6 = 27 ^ 4 * (2x – 5) e) x/(2 ^ 5) + (1/4) ^ 2 = (- 1/8) ^ 2 * x + 1/(2 ^ 3) b) 27 ^ 3 * 2 * x – 3 ^ 1 = 3 ^ 10 * x + 2 * 3 d) (4 ^ 5 * x + 32 ^ 2) * 2 ^ 5 = 2 ^ 16 . f) x/(4 ^ 4) – 1/((- 2) ^ 6) = – (- 1/16) ^ 2